Avaliação do potencial da arrecadação do ICMS no estado do Piauí - Ferreira, Sérgio Rodrigo Lebre (2010)
This study analyses the contribution of the construction industry for the country's growth, and provides a characterization of the housing programs that have already made and those that still are in the implementation phase in Piauí state. Using techniques of unit root and cointegration and based on quarterly data between 1994 and 2009, we test the existence of a long-run relationship between Brazillian GDP and Construction’s GDP. The results confirm the presence of this relationship for that period. From the results, it is clear the importance in investing in this sector to the growth of the country, and we can suggest that kind of investment as a long run development strategy to Piauí state.